Lead and strontium isotopes as tracers for Early Formative pottery exchange in ancient Mexico. (February 2021) - Renson, Virginie; Neff, Hector; Martínez-Cortizas, Antonio; Blomster, Jeffrey P.; Cheetham, David; Glascock, Michael D.
Abstract: The sourcing of ceramics contributes to resolve questions about the nature of interactions between ancient societies. One such question concerns the primacy of the Olmec center of San Lorenzo in the development of the first unified iconographic style and its role in the early evolution of Mesoamerican civilization. Applying a combination of the isotopic systems of lead and strontium to a selection of ceramics dating to Early Formative period (1500-1000 BCE), this research evaluates the isotopic approach as an independent tool to address previously debated questions. The results demonstrate the capacity of isotopic analyses to discriminate between production centers, identify imports, relate unassigned samples to their production center and ceramics to raw material, and produce insights into production strategies (ceramics used locally versus exports). It subsequently shows how this approach can help solving existing hypotheses relying on ceramic provenance in the Early Formative period in Ancient Mexico. The findings discussed in this study more largely demonstrate that the isotopic approach constitutes a powerful tool to source ceramics and should be considered where contradictory hypotheses exist on their provenance. Highlights: Pb and Sr isotopes are applied to Early Formative ceramics (Mesoamerica) for provenance purpose. Isotopic data identifies local production and imports, confirming elemental data. Isotopic data identifies source for samples unassigned based on elemental chemistry and establishes link with raw material. The isotopic approach improves our ability to source ceramics in Mesoamerica and addresses current hypotheses.